Waqf Unit Trust: sharī'ah issues and applications - Hasan, Aznan (IIiBF, International Islamic University of Malaysia, 2019)
This chapter discusses on the potentials of waqf unit trust as an alternative asset class promoting the sustainability of waqf funds. Waqf unit trust does not only cultivate philanthropic values through deeper public penetration but also encourage for effective waqf administration practice. Despite its potentials, waqf-unit trust is still at the inception stage, calling for more in-depth studies to explore its practicality from legal and Sharīʿah perspectives. This chapter, therefore, looks into Sharīʿah deliberations on the permissibility of the application of waqf unit trust in the context of the Malaysian waqf legal framework. It also brings attention to some proposed models, which can be useful reference for waqf stakeholders in structuring waqf unit trust products